Differences of lipid profile, body fat percentage, and waist circumference between childbearing age women acceptors of depot medroxy progesterone acetate contraceptive injection with non-acceptors in Padang City 2017 - Ariyasra, Utami; Reza, Mohamad; Arisanty, Dessy; Lipoeto, Nur Indrawaty (International Journal of Research in Medical Sciences, 2019)
Background: A hormonal contraception which considered ideal is depot medroxy progesteron acetat. There are large number of acceptors choose this contraception because this contraception is considered safe, effective, and can be used after labor. The possible side effect which can occur are increase of lipid profile, body fat percentage, and waist circumference. The purpose of this study is to see the differences between lipid profile, body fat percentage, and the waist circumference of women of childbearing age who use depot medroxy progesteron acetat injection compared with non-acceptors. Methods: This study was observational study with a cross sectional comparative approach and was conducted at the Regional Technical Services Unit (UPTD) at Regional Health Laboratory in West Sumatera Province from December 2017 until June 2018. The samples were 46 DMPA acceptors and 46 non-acceptors. The sampling method used random sampling technique. The measurements of lipid profile was conducted with colorimetric enzymatic method, which is GPO-PAP for triglycerides, and CHOD-PAP for total cholesterol, HDL and LDL. The percentage of body fat examination was conducted using Bioelectrical Impedance Analysis (BIA). The obtained data were analyzed by using t-test. Abnormal data were confirmed by Mann-whitney non-parametric test with p<0.05. Results: The results showed a significant difference between DMPA acceptors and non-acceptors (p<0.05). In total cholesterol (p = 0.000), LDL (p = 0.000), triglycerides (p = 0.000), body fat percentage (p = 0.007), body mass index (p = 0.004), and waist circumference (p = 0.001). But, in HDL there was no significant difference between DMPA acceptors and non-acceptors with p value = 0.302 (p>0.05). There were significant differences in total cholesterol, LDL, triglycerides, fat percentage, body mass index, and the circumference of waist in both DMPA acceptors and non acceptors. There were no significant difference in HDL levels between DMPA acceptors and non acceptors. Conclusions: There were significant differences in total cholesterol, LDL, triglycerides, fat percentage, body mass index, and waist circumference between DMPA acceptors and non-acceptors. There was no significant difference in HDL between DMPA acceptors and non-acceptors.